O MUSEU HISTÓRICO E A MEMÓRIA DA CIDADE DE PRESIDENTE PRUDENTE - Hélio Hirao (Universidade do Oeste Paulista, 2007)
This paper deals with the question of the Environmental Historic Patrimony of President Prudente SP, medium size city in the interior of São Paulo State and the necessity of Renovação and Revitalização Architectural of its Historical Museum and Municipal Archives. It discuss of the listed process and the importance in the formation of local identity. It analyzes the necessity of its adequacy to the new urban functions contemporaries.